Pembelajaran Inkuiri untuk Melatih Kemampuan Berpikir Tingkat Tinggi, Literasi Sains dan Keaktifan Siswa - Ercilina Anggri Destrilia; Rusdi Hasan; Rifa’i Rifa’i (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to determine the effect of the inquiry learning model on higher-order thinking skills, scientific literacy and activeness of class XI students at SMAN 09 Bengkulu City. The method used is a quasi-experimental (quasi-experimental) with a true experimental design pretest-posttest control group design. The results showed that the significance value of the Inquiry learning model on higher-order thinking skills was 0.002, scientific literacy was 0.000 and activeness was 0.000. There is no relationship between the inquiry learning model and higher-order thinking, scientific literacy and student activity. In conclusion, the inquiry learning model affects higher-order thinking skills, scientific literacy and student activity and produces better biology learning outcomes than conventional learning. Keywords: Higher Order Thinking, Student Activity, Inquiry Learning Model